2018
DOI: 10.1186/s13550-018-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic nerve activity after catheter-based renal denervation

Abstract: BackgroundCatheter-based renal sympathetic denervation (RDN) has been considered a potential treatment for therapy resistant hypertension (RHT). However, in a randomized placebo-controlled trial, RDN did not lead to a substantial blood pressure (BP) reduction. We hypothesized that variation in the reported RDN efficacy might be explained by incomplete nerve disruption as assessed by renal 123I–meta-iodobenzylguanidine (123I–mIBG) scintigraphy.MethodsIn 21 RHT patients (median age 60 years), we performed 123I–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Photon scattering from high liver radioactivity accumulation remains a challenge for the diagnosis of heart diseases (Kim et al 2010). Second, researches, such as 123 I-MIBG imaging involving therapy-resistant hypertension patients before and after catheter-based renal sympathetic denervation or kidney autotransplantation (Dobrowolski et al 2015(Dobrowolski et al , 2018, have proven the uptake of MIBG into kidney irrelevant to sympathetic nerve activity in the kidney, presumably due to its non-specific uptake via OCT2 or other transporters. Thus, a NET-selective tracer would open a new door for the diagnosis of renal sympathetic innervation.…”
Section: Net Tracer Specificity and Selectivitymentioning
confidence: 99%
“…Photon scattering from high liver radioactivity accumulation remains a challenge for the diagnosis of heart diseases (Kim et al 2010). Second, researches, such as 123 I-MIBG imaging involving therapy-resistant hypertension patients before and after catheter-based renal sympathetic denervation or kidney autotransplantation (Dobrowolski et al 2015(Dobrowolski et al , 2018, have proven the uptake of MIBG into kidney irrelevant to sympathetic nerve activity in the kidney, presumably due to its non-specific uptake via OCT2 or other transporters. Thus, a NET-selective tracer would open a new door for the diagnosis of renal sympathetic innervation.…”
Section: Net Tracer Specificity and Selectivitymentioning
confidence: 99%
“…Follow‐up duration ranged from 0.5 to 72 months. Ten studies reported data on plasma renin, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 nine studies on plasma aldosterone, 14 , 15 , 16 , 18 , 19 , 21 , 22 , 23 , 24 two studies on plasma norepinephrine, 20 , 25 seven studies on serum sodium, 23 , 24 , 26 , 27 , 28 , 29 , 30 nine studies on serum potassium, 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 five studies on urinary sodium, 18 , 20 , 24 , 26 , 33 and two studies on urinary potassium. 24 , 26 The characteristics of included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The greater the plasma renin activity, the more obvious the antihypertensive effect [ 45 ]. More studies indicated plasma renin activity did not significantly change post-RDN [ 46 48 ]. RDN also reduced whole-body norepinephrine spillover [ 49 ], did not significantly change plasma catecholamines [ 46 ], and had a mixed influence on aldosterone [ 45 , 47 , 48 , 50 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…More studies indicated plasma renin activity did not significantly change post-RDN [ 46 48 ]. RDN also reduced whole-body norepinephrine spillover [ 49 ], did not significantly change plasma catecholamines [ 46 ], and had a mixed influence on aldosterone [ 45 , 47 , 48 , 50 ]. In addition, arterial stiffness is a leading biomarker of risk in hypertension [ 51 ], and ferritin represents an independent risk factor of arterial stiffness [ 52 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%